RHAMNETIN IS A BETTER INHIBITOR OF SARS-COV-2 2’-O-METHYLTRANSFERASE THAN DOLUTEGRAVIR: A COMPUTATIONAL PREDICTION - Rowaiye, Adekunle B.; Oli, Angus Nnamdi; Onuh, Olukemi A.; W Emeter, Nkoli; Bur, Doofan; A. Obideyi, Oluwaseun; Cornelius Dayisi, Oluyomi; N. Akpa, Jude; Birah, Lovelyn; F. Omaka, Edward; Otibhor Iseghohi, Frances; Peace Otitoju, Akinbobola; et al. (African Journal of Infectious Diseases (AJID), 2022)
Background: The 2’-O-methyltransferase is responsible for the capping of SARS-CoV-2 mRNA and consequently the evasion of the host’s immune system. This study aims at identifying prospective natural inhibitors of the active site of SARS-CoV-2 2’O-methyltransferase (2’-OMT) through an in silico approach. Materials and Method: The target was docked against a library of natural compounds obtained from edible African plants using PyRx - virtual screening software. The antiviral agent, Dolutegravir which has a binding affinity score of -8.5 kcal mol−1 with the SARS-CoV-2 2’-OMT was used as a standard. Compounds were screened for bioavailability through the SWISSADME web server using their molecular descriptors. Screenings for pharmacokinetic properties and bioactivity were performed with PKCSM and Molinspiration web servers respectively. The PLIP and Fpocket webservers were used for the binding site analyses. The Galaxy webserver was used for simulating the time-resolved motions of the apo and holo forms of the target while the MDWeb web server was used for the analyses of the trajectory data. Results: The Root-Mean-Square-Deviation (RMSD) induced by Rhamnetin is 1.656A0 as compared to Dolutegravir (1.579A0). The average B-factor induced by Rhamnetin is 113.75 while for Dolutegravir is 78.87; the Root-Mean-Square-Fluctuation (RMSF) for Rhamnetin is 0.75 and for Dolutegravir is 0.67. Also at the active site, Rhamnetin also has a binding affinity score of -9.5 kcal mol−1 and forms 7 hydrogen bonds as compared to Dolutegravir which has -8.5 kcal mol−1 and forms 4 hydrogen bonds respectively. Conclusion: Rhamnetin showed better inhibitory activity at the target’s active site than Dolutegravir.